Corrosion Resistance of Al-Cu Alloys in Function of the Microstructure - Roman, Alejandra Silvina (2014)
Aluminum and its alloys are characterized by low density, high electrical and thermal conductivity, and good resistance to corrosion in certain media such as air. The mechanical strength alloy is achieved. The objective of the present research consist on studying the type of structure (columnar, equiaxed or with columnar to equiaxed transition, CET) using parameters of the solidification process and electrochemical parameters in Al, Cu and Al-Cu alloys with different concentrations. In order to obtain columnar, equiaxed and CET structures, the alloys were directionally solidified upwards in an experimental set up with a set of thermocouples in the samples which permit to determine the time dependent profiles during the process. The electrochemical studies of the samples were realized by using an electrochemical impedance spectroscopy (EIS) technique and potentio-dynamic polarization curves immersed in 3% NaCl solution at room temperature. In general, we observed that the susceptibility to corrosion of the different structures depends on the size of the secondary dendritic spacing and the proportion of Al2Cu phase and Al-rich phase.